2018
DOI: 10.1073/pnas.1720739115
|View full text |Cite|
|
Sign up to set email alerts
|

SLC39A14 deficiency alters manganese homeostasis and excretion resulting in brain manganese accumulation and motor deficits in mice

Abstract: Solute carrier family 39, member 14 (SLC39A14) is a transmembrane transporter that can mediate the cellular uptake of zinc, iron, and manganese (Mn). Studies of knockout () mice have documented that SLC39A14 is required for systemic growth, hepatic zinc uptake during inflammation, and iron loading of the liver in iron overload. The normal physiological roles of SLC39A14, however, remain incompletely characterized. Here, we report that mice spontaneously display dramatic alterations in tissue Mn concentrations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 78 publications
10
85
2
Order By: Relevance
“…In our Mn supplementation study, we fed mice with 300 ppm Mn and found a slight protective effect against DSS‐induced colitis. Previous mouse studies have shown that oral supplementation with Mn even at levels of ~2400 ppm does not cause toxicity . This finding suggests that Mn toxicity would be less of a concern in the design of dietary Mn supplementation for this IBD mouse model.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…In our Mn supplementation study, we fed mice with 300 ppm Mn and found a slight protective effect against DSS‐induced colitis. Previous mouse studies have shown that oral supplementation with Mn even at levels of ~2400 ppm does not cause toxicity . This finding suggests that Mn toxicity would be less of a concern in the design of dietary Mn supplementation for this IBD mouse model.…”
Section: Resultsmentioning
confidence: 58%
“…Previous mouse studies have shown that oral supplementation with Mn even at levels of ~2400 ppm does not cause toxicity. 51,52 This finding suggests that Mn toxicity would be less of a concern in the design of dietary Mn supplementation for this IBD mouse model. Future studies will be needed to determine the dietary Mn levels that would be most beneficial for human patient populations.…”
Section: Discussionmentioning
confidence: 82%
“…Even more recently, a syndrome of infantile‐ or childhood‐onset dystonia with hypermanganesemia (OMIM #617013) has been linked to biallelic mutations in yet another divalent cation transporter gene, SLC39A14 , responsible for manganese elimination . This disorder presents in infancy or early childhood with developmental delay, dystonia, and bulbar dysfunction .…”
Section: The “Top Ten” Of Treatable Iems Presenting With Movement Dismentioning
confidence: 99%
“…We did so since there are important gene expression data on metal transporters that modulate influx and efflux of Mn from the gastrointestinal tract after dietary ingestion and its release into the bloodstream. 23,24 The amount of Mn available to a tumour, be it at primary or metastatic sites, will initially be determined by how much Mn passes through this gateway into the bloodstream. Laser ablation was carried out on a standard glass slide on which an unstained section of patient material, derived from a tissue microarray, had been cut at 5 mm thickness from a formalin-fixed paraffin-embedded (FFPE) block.…”
Section: Controls and Standards From Normal Tissuesmentioning
confidence: 99%
“…This dual system controls Mn levels in the blood via the influx and efflux metal transporters in the liver and bile duct epithelium: predominantly via SLC39A14 (Mn uptake by the liver) and SLC30A10 (Mn efflux via the bile duct epithelium). 23,24 If these transporters are altered by mutation, allelic variants, or regulatory elements, the level of Mn in the blood is changed. When this occurs, dietary Mn uptake by the liver is reduced, more Mn is directed into the blood, and higher than normal concentrations accumulate in organs such as the brain.…”
Section: Mn Uptake and Its Distribution In Normal Tissues/organsmentioning
confidence: 99%